Proceedings of the 7th Biannual International Symposium on Nasopharyngeal Carcinoma 2015. Issue 1 (April 2016) - Tan, IB; Chang, Ellen; Chen, Chien-Jen; Hsu, Wan-Lun; Chien, Yin-Chu; Hildesheim, Allan; McKay, James; Gaborieau, Valerie; Kaderi, Mohamed; Purnomosari, Dewajani; Voegele, Catherine; LeCalvez-Kelm, Florence; et al.
Table of contents A1 Hope and despair in the current treatment of nasopharyngeal cancer IB Tan I1 NPC international incidence and risk factors Ellen T Chang I2 Familial nasopharyngeal carcinoma and the use of biomarkers Chien-Jen Chen, Wan-Lun Hsu, Yin-Chu Chien I3 Genetic susceptibility risk factors for sporadic and familial NPC: recent findings Allan Hildesheim I5 Genetic and environmental risk factors for nasopharyngeal cancer in Southeast Asia James D McKay, Valerie Gaborieau, Mohamed Arifin Bin Kaderi, Dewajani Purnomosari, Catherine Voegele, Florence LeCalvez-Kelm, Graham Byrnes, Paul Brennan, Beena Devi I6 Characterization of the NPC methylome identifies aberrant epigenetic disruption of key signaling pathways and EBV-induced gene methylation Li L, Zhang Y, Fan Y, Sun K, Du Z, Sun H, Chan AT, Tsao SW, Zeng YX, Tao Q I7 Tumor exosomes and translational research in NPC Pierre Busson, Claire Lhuillier, Olivier Morales, Dhafer Mrizak, Aurore Gelin, Nikiforos Kapetanakis, Nadira Delhem I8 Host manipulations of the Epstein-Barr virus EBNA1 protein Sheila Mansouri, Jennifer Cao, Anup Vaidya, and Lori Frappier I9 Somatic genetic changes in EBV-associated nasopharyngeal carcinoma Lo Kwok Wai I10 Preliminary screening results for nasopharyngeal carcinoma with ELISA-based EBV antibodies in Southern China Sui-Hong Chen, Jin-lin Du, Ming-Fang Ji, Qi-Hong Huang, Qing Liu, Su-Mei Cao I11 EBV array platform to screen for EBV antibodies associated with NPC and other EBV-associated disorders Denise L. Doolan, Anna Coghill, Jason Mulvenna, Carla Proietti, Lea Lekieffre, Jeffrey Bethony, and Allan Hildesheim I12 The nasopharyngeal carcinoma awareness program in Indonesia Renske Fles, Sagung Rai Indrasari, Camelia Herdini, Santi Martini, Atoillah Isfandiari, Achmad Rhomdoni, Marlinda Adham, Ika Mayangsari, Erik van Werkhoven, Maarten Wildeman, Bambang Hariwiyanto, Bambang Hermani, Widodo Ario Kentjono, Sofia Mubarika Haryana, Marjanka Schmidt, IB Tan I13 Current advances and future direction in nasopharyngeal cancer management Brian O'Sullivan I14 Management of juvenile nasopharyngeal cancer Enis Ozyar I15 Global pattern of nasopharyngeal cancer: correlation of outcome with access to radiotherapy Anne WM Lee I16 The predictive/prognostic biomarker for nasopharyngeal carcinoma Mu-Sheng Zeng I17 Effect of HLA and KIR polymorphism on NPC risk Xiaojiang Gao, Minzhong Tang, Pat Martin, Yi Zeng, Mary Carrington I18 Exploring the Association between Potentially Neutralizing Antibodies against EBV Infection and Nasopharyngeal Carcinoma Anna E Coghill, Wei Bu, Hanh Nguyen, Wan-Lun Hsu, Kelly J Yu, Pei-Jen Lou, Cheng-Ping Wang, Chien-Jen Chen, Allan Hildesheim, Jeffrey I Cohen I19 Advances in MR imaging in NPC Ann D King O1 Epstein-Barr virus seromarkers and risk of nasopharyngeal carcinoma: the gene-environment interaction study on nasopharyngeal carcinoma in Taiwan Yin-Chu Chien, Wan-Lun Hsu, Kelly J Yu, Tseng-Cheng Chen, Ching-Yuan Lin, Yung-An Tsou, Yi-Shing Leu, Li-Jen Laio, Yen-Liang Chang, Cheng-Ping Wang, Chun-Hun Hua, Ming-Shiang Wu, Chu-Hsing Kate Hsiao, Jehn-Chuan Lee, Ming-Hsui Tsai, Skye Hung-Chun Cheng, Pei-Jen Lou, Allan Hildesheim, Chien-Jen Chen O2 Familial tendency and environmental co-factors of nasopharyngeal carcinoma: the gene-environment interaction study on nasopharyngeal carcinoma in Taiwan Wan-Lun Hsu, Kelly J Yu, Yin-Chu Chien, Tseng-Cheng Chen, Ching-Yuan Lin, Yung-An Tsou, Yi-Shing Leu, Li-Jen Liao, Yen-Liang Chang, Tsung-Lin Yang, Chun-Hun Hua, Ming-ShiangWu, Chu-Hsing Kate Hsiao, Jehn-ChuanLee, Ming-Hsui Tsai, Skye Hung-Chun Cheng, Jenq-Yuh Ko, Allan Hildesheim, Chien-Jen Chen O3 The genetic susceptibility and prognostic role of TERT-CLPTM1L and genes in DNA damage pathways in NPC Josephine Mun Yee Ko, Wei Dai, Dora Kwong, Wai Tong Ng, Anne Lee, Roger Kai Cheong Ngan, Chun Chung Yau, Stewart Tung, Maria Li Lung O4 Long term effects of NPC screening Mingfang Ji, Wei Sheng, Mun Hon Ng, Weimin Cheng, Xia Yu, Biaohua Wu, Kuangrong Wei, Jun Zhan, Yi Xin Zeng, Su Mei Cao, Ningshao Xia, Yong Yuan O5 Risk prediction of nasopharyngeal carcinoma by detecting host genetic and Epstein-Barr virus variation in saliva Qian Cui, Miao Xu, Jin-Xin Bei, Yi-Xin Zeng O6 Patterns of care study in Turkish nasopharyngeal cancer patients (NAZOTURK): A Turkish Radiation Oncology Association Head and Neck Cancer Working Group Study B Şahin, A Dizman, M Esassolak, A Saran İkizler, HC Yıldırım, M Çaloğlu, B Atalar, F Akman, C Demiroz, BM Atasoy, E Canyilmaz, S Igdem, G Ugurluer, T Kütük, M Akmansoy, E Ozyar O7 Long term outcome of intensity modulated radiotherapy in nasopharyngeal carcinoma in National Cancer Centre Singapore Kiattisa Sommat, Fu Qiang Wang, Li-Lian Kwok, Terence Tan, Kam Weng Fong, Yoke Lim Soong, Shie Lee Cheah, Joseph Wee O8 International phase II randomized study on the addition of docetaxel to the combination of cisplatin and 5-fluorouracil in the induction treatment for nasopharyngeal carcinoma in children and adolescents M Casanova, E Özyar, C Patte, D Orbach, A Ferrari, VF Cristine, H Errihani, J Pan, L Zhang, S Liji, K Grzegorzewski, L Gore, A Varan O9 Prognostic impact of metastatic status in patients with nasopharyngeal carcinoma Susanna Hilda Hutajulu, Guntara Khuzairi, Camelia Herdini, Henry Kusumo, Mardiah Suci Hardianti, Kartika Widayati Taroeno-Hariadi, Ibnu Purwanto, Johan Kurnianda O10 Development of small molecule inhibitors of latent Epstein-Barr virus infection for the treatment of nasopharyngeal carcinoma Troy E. Messick, Kimberly Malecka, Lois Tolvinski, Samantha Soldan, Julianna Deakyne, Hui Song, Antonio van den Heuvel, Baiwei Gu, Joel Cassel, Mark McDonnell, Garry R Smith, Venkata Velvadapu, Haiyan Bian, Yan Zhang, Marianne Carlsen, Shuai Chen, Alastair Donald, Christian Lemmen, Allen B Reitz, Paul M Lieberman O11 Therapeutic targeting of cancer stem-like cells using a Wnt modulator, ICG-001, enhances the treatment outcome of EBV-positive nasopharyngeal carcinoma King Chi Chan, Lai Sheung Chan, Kwok Wai Lo, Timothy Tak Chun Yip, Roger Kai Cheong Ngan, Michael Kahn, Maria Li Lung, Nai Ki Mak O12 Role of micro-RNA in NPC biology Fei-Fei Liu O13 Expansion of EBNA1- and LMP2-specific effector T lymphocytes from patients with nasopharyngeal carcinoma without enhancement of regulatory T cells Wafa Khaali; Juliette Thariat; Laurence Fantin; Flavia Spirito; Meriem Khyatti; El Khalil Ben Driss; Sylvain Olivero; Janet Maryanski; Alain Doglio O14 The experience of patients' life after amifostine radiotherapy treatment (ART) for nasopharyngeal carcinoma (NPC) Mengxue Xia, Yunfei Xia, Hui Chang, Rachel Shaw O15 Analysis of mitochondrial DNA mutation in latent membrane protein-1 positive nasopharyngeal carcinoma Pudji Rahaju O16 Factors influencing treatment adherence of nasopharyngeal cancer and the clinical outcomes: a hospital-based study Mardiah Suci Hardianti, Sindhu Wisesa, Kartika Widayati Taroeno-Harijadi, Ibnu Purwanto, Bambang Hariwiyanto, Wigati Dhamiyati, Johan Kurnianda O17 Chromosomal breaks mediated by bile acid-induced apoptosis in nasopharyngeal epithelial cells: in relation to matrix association region/scaffold attachment region Sang-Nee Tan, Sai-Peng Sim O18 Expression ofp53 (wild type) on nasopharyngeal carcinoma stem cell that resistant to radiotherapy Muhtarum Yusuf, Ahmad C Romdhoni, Widodo Ario K, Fedik Abdul Rantam O19 Mathematical model of nasopharyngeal carcinoma in cellular level Sugiyanto, Lina Aryati, Fajar Adi-Kusumo, Mardiah Suci Hardianti O20 Differential expression of microRNA-21 on nasopharyngeal carcinoma plasma patient SY Bintoro, R Oktriani, C. Herawati, A Surono, Sofia M. Haryana O21 Therapeutic targeting of an oncogenic fibroblast growth factor-FGF19, which promotes proliferation and induces EMT of carcinoma cells through activating ERK and AKT signaling L. Zhong, L. Li, B. B. Ma, A. T. Chan, Q. Tao O22 Resist nasopharyngeal carcinoma (NPC): next generation T cells for the adoptive immunotherapy of NPC M. Kalra, M. Ngo, S. Perna, A. Leen, N. Lapteva, C. M. Rooney, S. Gottschalk O23 The correlation of heat shock protein 70 expressions and staging of nasopharyngeal carcinoma Elida Mustikaningtyas, Sri Herawati, Achmad C Romdhoni O24 Epstein-Barr virus serological profiles of nasopharyngeal carcinoma - A tribute to Werner Henle Mingfang Ji, YaruiXu, Weimin Cheng, ShengxiangGe, Fugui Li, M. H. Ng O25 Targeting the apoptosis pathway using combination TLR3 agonist with anti-survivin molecule (YM-155) in nasopharyngeal carcinoma Louise SY Tan, Benjamin Wong, CM Lim O26 The resistance mechanism of nasopharyngeal cancer stem cells to cisplatin through expression of CD44, Hsp70, p53 (wild type), Oct-4, and ß-catenin encoded-genes Achmad C Romdhoni, Fedik A. Rantam, Widodo Ario Kentjono P1 Prevalence of nasopharyngeal carcinoma patients at Departement of Otorhinolaringology-Head and Neck Surgery, Dr. Hasan Sadikin general hospital, Bandung, Indonesia in 2010-2014 Deasy Z Madani, Nur Akbar, Agung Dinasti Permana P2 Case report on pediatric nasopharyngeal carcinoma at Dr. Sardjito Hospital, Yogyakarta Camelia Herdini, Sagung Rai Indrasari, Jajah Fachiroh, Dwi Hartati, T. Baning Rahayudjati P3 Report on loco regionally advanced nasopharyngeal cancer patients treated with induction chemotherapy followed by concurrent chemo-radiation therapy Iswandi Darwis, Susanna Hilda Hutajulu, Bambang Hariwiyanto, Wigati Dhamiyati, Ibnu Purwanto, Kartika Widayati Taroeno-Hariadi, Johan Kurnianda P4 Sex and age differences in the survival of patients with nasopharyngeal carcinoma Sindhu Wisesa, Mardiah Suci Hardianti, Susanna Hilda Hutajulu, Kartika Widayati Taroeno-Harijadi, Ibnu Purwanto, Camelia Herdini, Wigati Dhamiyati, Johan Kurnianda P5 Impact of delayed diagnosis and delayed therapy in the treatment outcome of patients with nasopharyngeal carcinoma Khoirul Anwar, Susanna Hilda Hutajulu, Sagung Rai Indrasari, Sri Retna Dwidanarti, Ibnu Purwanto, Kartika Widayati Taroeno-Hariadi, Johan Kurnianda P6 Anaysis of pretreatment anemia in nasopharyngeal cancer patients undergoing neoadjuvant therapy Dominicus Wendhy Pramana, Susanna Hilda Hutajulu, Bambang Hariwiyanto, Wigati Dhamiyati, Ibnu Purwanto, Kartika Widayati Taroeno-Hariadi, Johan Kurnianda P7 Results of treatment with neoadjuvant cisplatin-5FU in locally advanced nasopharyngeal carcinoma: a local experience Diah Ari Safitri, Susanna Hilda Hutajulu, Camelia Herdini, Sri Retna Dwi Danarti, Ibnu Purwanto, Kartika Widayati Taroeno-Hariadi, Johan Kurnianda P8 Geriatrics with nasopharyngeal cancer Suryo A Taroeno, Sindhu Wisesa, Kartika Widayati Taroeno-Hariadi, Ibnu Purwanto, Bambang Hariwiyanto, Wigati Dhamiyati, Johan Kurnianda P9 Correlation of lymphocyte to monocyte and neutrophil to lymphocyte ratio to the response of cisplatin chemoradiotheraphy in locally advance nasopharyngeal carcinoma I. Wijaya, A. Oehadian, D. Prasetya P10 Prediction of nasopharyngeal carcinoma risk by Epstein-Barr virus seromarkers and environmental co-factors: the gene-environment interaction study on nasopharyngeal carcinoma in Taiwan Wan-Lun Hsu, Yin-Chu Chien, Kelly J Yu, Cheng-Ping Wang, Ching-Yuan Lin, Yung-An Tsou, Yi-Shing Leu, Li-Jen Liao, Yen-Liang Chang191, 192, Jenq-Yuh Ko, Chun-Hun Hua, Ming-Shiang Wu, Chu-Hsing Kate Hsiao, Jehn-Chuan Lee, Ming-Hsui Tsai, Skye Hung-Chun Cheng, Pei-Jen Lou, Allan Hildesheim, Chien-Jen Chen P11 Non-viral risk factors for nasopharyngeal carcinoma in West Sumatra, Indonesia Sukri Rahman, Bestari J. Budiman, Novialdi, Rahmadona, Dewi Yuri Lestari P12 New prototype Vidas EBV IgA quick: performance on Chinese and Moroccan populations C. Yin, A. Foussadier, E. Blein, C. Chen, N. Bournet Ammour, M. Khiatti, S. Cao P13 The expression of EBV-LMP1 and VEGF as predictors and plasma EBV-DNA levels as early marker of distant metastasis after therapy in nasopharyngeal cancer Dewi Syafriyetti Soeis Marzaini P14 Characteristics and factors influencing subjects refusal for blood samples retrieval: lesson from NPC case control study in Yogyakarta – Indonesia Dwi Hartati, Baning Rahayujati, Camelia Herdini, Jajah Fachiroh P15 Expression of microRNA BART-7-3p and mRNA PTEN on blood plasma of patients with nasopharyngeal carcinoma L. Gunawan, S. Mubarika Haryana, A. Surono, C. Herawati P16 IgA response to native early antigen (IgA-EAext) of Epstein-Barr virus (EBV) in healthy population and nasopharyngeal carcinoma (NPC) patients: the potential for diagnosis and screening tools Michael Hartono, Jajah Fachiroh, Umi Intansari, Dewi Kartikawati Paramita P17 IgA responses against Epstein-Barr Virus Early Antigen (EBV-EA) peptides as potential candidates of nasopharyngeal carcinoma detection marker Akmal Akbar, Jajah Fachiroh, Dewi Kartikawati Paramita P18 Association between smoking habit and IgA-EBV titer among healthy individuals in Yogyakarta, Indonesia Benny Hermawan, T Baning Rahayudjati, Dewi K Paramita, Jajah Fachiroh P19 Epstein-Barr virus IgA titer comparison of healthy non-family individuals and healthy first degree family of NPV patients Gabriella Argy, Jajah Fachiroh, Dewi Kartikawati Paramita, Susanna Hilda Hutajulu P20 Identification of EBV Early Antigen (EA) derived peptides for NPC diagnosis Theodora Caroline Sihotang, Jajah Fachiroh, Umi Intansari, Dewi Kartikawati Paramita P21 Host-pathogen study: relative expression of mRNA BRLF1 Epstein-Barr virus as a potential biomarker for tumor progressivity and polymorphisms ofTCRBC andTCRGC2 host genes related to genetic susceptibility on nasopharyngeal carcinoma Daniel Joko Wahyono, Purnomo Soeharso, Dwi Anita Suryandari, Lisnawati, Zanil Musa, Bambang Hermani P22In vitro efficacy of silvestrol and episilvestrol, isolated from Borneo, on nasopharyngeal carcinoma, a major cancer in Borneo Maelinda Daker, Yeo Jiun Tzen, Norhasimah Bakar, Asma' Saiyidatina Aishah Abdul Rahman, Munirah Ahmad, Yeo Tiong Chia, Alan Khoo Soo Beng P23 The expression of mir-141 in patients with nasopharyngeal cancer Widyandani Sasikirana, Tirta Wardana, Muhammad Radifar, Cita Herawati, Agus Surono, Sofia Mubarika Haryana